The dilemma of wildfire definition: what it reveals and what it implies - Tedim, Fantina (2020)
This paper presents the results of an explorative survey, based on a questionnaire sent by email, about how wildfire experts, operating in different countries, perceive wildfire and express their mindset by defining "wildfire" from a list of 14 terms and how they justify their preference for the term selected as the most important. Using a five-point Likert Scale, results from 221 valid replies indicate a general convergence toward a reduced number of terms. Six of them exhibit a mean >3.20 (Disturbance, Natural hazard, Climate-sensitive hazard, Socio-ecological hazard, Socio-ecological disturbance, and Social-ecological hazard). The three most preferred terms (i.e., Disturbance, Natural hazard, and Climate-sensitive hazard) reflect wildfire as a natural process or phenomenon (about 59% of the replies). The three terms characterized by both the social and ecological adjectives (i.e., Socio-ecological hazard, Socio-ecological disturbance, Social-ecological hazard) occupy relatively less favorable positions in the ranking. For each term, a synthesis of the explanations given by the respondents is provided, together with a critical comment. Our findings show very different perceptions of wildfires inclusively within the same disciplinary field. In addition, for the same term selected, different definitions are often presented. This reflects sectorial, disciplinary, and personal perspectives of the wildfire phenomenon and the lack of a common understanding of wildfire "nature" (i.e., its own identity). The different perceptions on wildfire concept influence the knowledge that can be used by decision makers to improve wildfire management policies. This work puts into perspective one of the most widespread problems in science: the lack of appropriate and similar terminology across different scientific fields dealing with the same problem. A common conceptualization of the nature of wildfires and the creation of a common language across different scientific fields related to wildfires is of paramount importance to address the complexity of the existing problems, and enhance an interactive communication not only among scientific community but also with stakeholders and citizens.